2007
DOI: 10.17305/bjbms.2007.3019
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome Aberrations as Bioindicators of Environmental Genotoxicity

Abstract: Due to the exposure to various potentially genotoxic xenobiotics, derived from recent war activities such as NATO air strikes with antitank ammunition containing depleted uranium, we have evaluated chromosome aberrations in 84 peripheral blood samples from three local populations. One population sample included 30 individuals who lived in the Sarajevo area during and after the war (exposed to potential genotoxins), second population was presented with 26 employees of the tank repair facility in Hadzići (target… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 5 publications
2
6
0
Order By: Relevance
“…Numerous studies confirmed that age could have confounding effect on chromosome aberration frequencies (31). In this study, a significant effect of age and gender on the frequency of aneuploidies was demonstrated.…”
Section: Discussionsupporting
confidence: 72%
“…Numerous studies confirmed that age could have confounding effect on chromosome aberration frequencies (31). In this study, a significant effect of age and gender on the frequency of aneuploidies was demonstrated.…”
Section: Discussionsupporting
confidence: 72%
“…There are numerous other studies that demonstrate the deleterious effects of DU on viability, micronuclei, chromosomal instability, and sister chromatid exchanges by human bronchial, bone marrow, and Chinese hamster ovary cells (Kennedy and Saluga, 1970;Kadhim et al, 1992Kadhim et al, , 1994Nagasawa and Little, 1992;Lin et al, 1993;Schroder et al, 2003;Stearns et al, 2005;Holmes et al, 2014). Osteosarcoma risk has clearly been demonstrated to be related to the amount of radiation exposure, and there is a wealth of in vitro studies of bone cells and animal models that illustrate this (Miller et al, 1998a(Miller et al, , 2001(Miller et al, , 2003(Miller et al, , 2005Ibrulj et al, 2004Ibrulj et al, , 2007Miller and McClain, 2007). Osteosarcoma risk has clearly been demonstrated to be related to the amount of radiation exposure, and there is a wealth of in vitro studies of bone cells and animal models that illustrate this (Miller et al, 1998a(Miller et al, , 2001(Miller et al, , 2003(Miller et al, , 2005Ibrulj et al, 2004Ibrulj et al, , 2007Miller and McClain, 2007).…”
Section: Bonesmentioning
confidence: 99%
“…And certainly -it has to do with depleted uranium usage". Ibrulj et al (2007) studied the peripheral lymphocyte genes in the people in Hadžići likely exposed to DU and those in a control area where no DU was used. They found a statistically significant increase in the chromosome aberration frequency in the exposed group in 2007.…”
Section: Gulf War Syndrome Among Veteransmentioning
confidence: 99%